2007
DOI: 10.1158/0008-5472.can-06-3490
|View full text |Cite
|
Sign up to set email alerts
|

Short Telomere Length and Breast Cancer Risk: A Study in Sister Sets

Abstract: Telomeres consist of a tandem repeats of the sequence TTAGGG at the ends of chromosomes and play a key role in the maintenance of chromosomal stability. Previous studies indicated that short telomeres are associated with increased risk for human bladder, head and neck, lung, and renal cell cancer. We investigated the association between white blood cell telomere length and breast cancer risk among 268 family sets (287 breast cancer cases and 350 sister controls). Telomere length was assessed by quantitative PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 48 publications
9
132
1
Order By: Relevance
“…Three independent studies of bladder cancer found that individuals with bladder cancer had shorter telomeres in either blood or buccal cells than healthy control subjects (Broberg et al 2005;McGrath et al 2007;Wu et al 2003). Similar findings were noted in patients with head, neck, lung, and breast cancers (Shen et al 2007;Wu et al 2003). In these studies, telomere length differences between cases and controls were statistically significant, but the profound telomere shortening seen in DC was not present in germline DNA from these cases.…”
Section: Other Complex Disorders Associated With Short Telomeresmentioning
confidence: 69%
“…Three independent studies of bladder cancer found that individuals with bladder cancer had shorter telomeres in either blood or buccal cells than healthy control subjects (Broberg et al 2005;McGrath et al 2007;Wu et al 2003). Similar findings were noted in patients with head, neck, lung, and breast cancers (Shen et al 2007;Wu et al 2003). In these studies, telomere length differences between cases and controls were statistically significant, but the profound telomere shortening seen in DC was not present in germline DNA from these cases.…”
Section: Other Complex Disorders Associated With Short Telomeresmentioning
confidence: 69%
“…In addition, it has been suggested that measuring telomere length may help predict risk of occurrence of certain types of cancer [22][23][24] including BRCA mutationassociated breast cancer [25,26]. There is some evidence to suggest that exercise may affect telomere length.…”
Section: Introductionmentioning
confidence: 99%
“…Telomeres are of great importance in maintaining chromosomal stability and cellular DNA damage and repair (Hahn, 2003;Callen and Surralles, 2004;Blasco, 2005;Rodier et al, 2005). Short average telomere length in peripheral blood appears to be a susceptibility marker for human breast, bladder, head and neck, lung, and renal cell cancers (Wu et al, 2003;Broberg et al, 2005;Shen et al, 2007;Jang et al, 2008) and meta studies show that the presence of shortened telomeres is a marker for susceptibility to human cancer, but for which cancer types is not clearly established Wentzensen et al, 2011). Short telomere length caused chromosomal instability and epithelial carcinogenesis in mice (Artandi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%